Dominant taxa, rather than Shannon diversity, drive zooplankton stability across scales - Zeng Lei; Zhang Rui; Chen Yuxiang; Liu Beibei; Zheng Tingting; Li Wuhui; Tang Yuqi; Li Yating; Xiang Yuqi; Nie Mengwei; Chen Guobao (Estuarine, Coastal and Shelf Science, 2026)

Structural characterization and in vivo and in vitro anti-osteoporosis potential of two Psoralea corylifolia L. polysaccharides - Jing Yang; Ziling Tang; Chanjuan Chen; Pei Lin; Ye He; Xinsheng Yao; Beibei Zhang; Zhihong Yao; Zuocheng Qiu; Zifei Qin (Carbohydrate Polymers, 2026)

REE source, fractionation and enrichment behavior in the Tuguanzhai-Maliping ion-adsorption REE deposit, Tengchong Block (SW China) - Zhong Tang; Congfa Bao; Tianxue Ming; Hanjie Wen; Xiaohu He; Hao Cheng; Jiaxin Liu; Zewei Pan; Liang Li; Jiasheng Wang; BeiBei Chen; Kunfeng Qiu (Acta Geochimica, 2026)

Genome Analysis and Reproductive Observations Suggest Allotetraploidy and a Potential Reproduction–Metabolism Association in the Endangered Fish Neolissochilus heterostomus - Tiaoyi Xiao; Zhichao Wu; Dongfang Li; Beibei Qin; Shengguo Tang; Chengyi Lin; Kuayun Mao; Jinwu Yin; Zhihu Li; Hongquan Wang; Zhao Lv (Fishes, 2026)
Neolissochilus heterostomus, a cyprinid fish endemic to Yunnan Province, China, is highly valued for both ornamental and edible purposes, yet its wild populations are currently declining and classified as endangered. In this study, we present a chromosome-level genome assembly of N. heterostomus, utilizing the PacBio HiFi and Hi-C strategies. The assembled genome spans 1793.99 Mb and is anchored to 50 chromosomes, comprising a total of 50,203 genes. Genomic features and chromosomal karyotype data recorded in the present study are consistent with an allotetraploid origin for N. heterostomus. Comparative genomics shows that N. heterostomus shares a close phylogenetic relationship with another allotetraploid fish, the common carp Cyprinus carpio. In total, 4687 expanded and 1365 contracted gene families were identified in N. heterostomus. Further enrichment analyses indicated an overrepresentation of metabolism-related pathways among the expanded and positively selected gene families, whereas the contracted gene families were enriched in reproduction- and embryonic development-related pathways. Reproductive observations further indicate that N. heterostomus produces fewer eggs than other cyprinid species characterized by relatively long embryonic development periods (106.1 h; accumulated temperature: 2260.6 °C·h), including common carp, goldfish (Carassius auratus), grass carp (Ctenopharyngodon idella), pond loach (Misgurnus anguillicaudatus), and blunt snout bream (Megalobrama amblycephala). These findings suggest a potential association between metabolism-related genomic features and reproductive traits, although functional validation remains necessary. Overall, this study may offer insights into the polyploidization, metabolic, and reproductive traits of N. heterostomus, thereby providing genomic and biological resources that may support future studies relevant to the conservation and management of this endangered species.

Targeting the TOPK-STAT3 pathway in keratinocytes and mast cells mediates the therapeutic attenuation of Atopic dermatitis - Xiaohan Du; Xianshuai Shi; Qian He; Zheng Yuan; Longzhen Cui; Beibei Tang; Shuang Zhao; Yafang Li; Lei Ma; Mee-Hyun Lee; Olesya S. Malyarenko; Juanjuan Xiao; et al. (Inflammation Research, 2026)

Smart autologous plasma-ICG self-assembled carriers prolong half-life of growth factors and enhance antibacterial effect for periodontitis therapy - Hailun Zhou; Jun Zhou; Xiaoqi Wang; Li Tang; Cong Liu; Chunyun Liang; Hejia Qin; Shufang Zhuo; Ao Long; Fengyuan Zhou; Lu Liu; Wenjin Chen; et al. (Chemical Engineering Journal, 2026)

Enhancing Doxorubicin Bioavailability via Dissolving Microneedles: Roles of Drug Loading and Administration Force - Beibei Yang; Huanhuan Pan; Chunxian Zhou; Jingxin Yang; Wentao Wu; Wenjing Tang; Xin Pan; Chuanbin Wu; Tingting Peng (AAPS PharmSciTech, 2026)

Analyzing the metabolic mechanisms and regulation of flavor compounds in Baijiu from a microbial sociology perspective - Beibei Li; Jie Tang; Chutian Zhu; Jiaxin Gong; Qun Wu; Yong Yang; Xiangyang Ge; Junlin Wei; Yongguang Huang (Food Bioscience, 2026)

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

Daily Arctic first-year sea ice thickness observed by China’s GNSS-R satellite constellation - Yuan Li; Lei Zheng; Qi Liang; Teng Li; Chuyue Peng; Lian He; Qiuyang Zhao; Zhuoqi Chen; Qi Tang; Ying Li; Beibei Liang; Shengli Wu; et al. (Science Bulletin, 2026)

Coupled effects of biochar nanoparticles aging and transport on rare earth element immobilization and carbon sequestration - Quan Wan; Miaoyue Zhang; Beibei Liu; Erwin Klumpp; Roland Bol; Yuan Dai; Man Zhao; Shizhong Wang; Yetao Tang; Jean Louis Morel; Stéphanie Ouvrard; Chao Jin; et al. (Journal of Environmental Sciences, 2026)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Aqueous photochemistry of brown carbon: H2O2 formation, enhanced SO2 oxidation, and the real role of excited triplets - Beibei Liu; Lingdong Kong; Yixuan An; Yu Lu; Yuwen Wang; Jie Tan; Xingfu Tang; Lin Wang (Atmospheric Environment, 2025)

The vascular preferentially expressed OsCOPT7 mediates the long-distance transport of copper in rice - Hui Zhou; Haiyang Tang; Beibei Hu; Jin Zhang; Yuan Qin; Fanrong Zeng; Guang Chen; Zhong-Hua Chen; Fenglin Deng (Plant and Soil, 2025)

Experimental investigation of the effect of ventilation rate on the vertical forward smoldering propagation of Yunnan lignite - Dengke Su; Yibo Tang; Dongjuan Ma; Jiateng Chen; Shenyu Li; Beibei Jia (Process Safety and Environmental Protection, 2025)

Characterization of endophytic bacterial communities in Abelmoschus manihot under Cd stress and isolation of Cd-resistant bacteria - Mengxi Wu; Tingting Tang; Qilin Liu; Peng Xiao; Yibo Xiong; Jiahui Feng; Minrui Peng; Jungang Zhu; Xue Yong; Yin Jia; Beibei Jiang; Yezhang Ding; et al. (Journal of Hazardous Materials, 2025)

Controlling the underground spontaneous combustion of coal using an expansive aerosol - Xiao Mao; Yibo Tang; Dongjuan Ma; Shenyu Li; Beibei Jia; Jiateng Chen (Fuel, 2025)

KOH-etched carbon fibre cathode exhibiting enhanced U(VI) and organic pollutants removal in a solar wastewater resourcezation system via surface modification - Beibei Gao; Rongzhong Wang; Qingyan Zhang; Guolong Tang; Qingqing Yang; Yunjiao Hao; Yanlin Chen; Qingyi Zeng (Process Safety and Environmental Protection, 2025)

“Turn-on-off” Fluorescent Probes Based on Carbon Nanoparticles for Hypochlorite and Fe2+ Detection - Minhui Wang; Xuemei Dong; Beibei Guo; Dinghai Wang; Yecang Tang (Journal of Fluorescence, 2025)

Mechanism influence on the coexistence of two anions on redox kinetics and volume effect of CoPSe as anode material for potassium-ion batteries and potassium-ion hybrid capacitors - Xiujuan Wang; Jiamei Wang; Yingying Wang; Ruihao Chen; Jing Qin; Tang Ouyang; Hongyu Wei; Hao Jing; Guanghui Yuan; Beibei Wang; Gang Wang (Chemical Engineering Journal, 2024)

Self-supporting CoFe2O4 nanoparticles on 2D g-C3N4/2D loofah activated carbon mediated peroxymonosulfate activation for tetracycline degradation - Beibei Niu; Wenjun Li; Na Geng; Shuaichen Li; Wangshu Tang; Xiaoxiao Zhang; Congshu Huang; Jianzhi Wang (Journal of Environmental Chemical Engineering, 2024)

Advanced analytical techniques for authenticity identification and quality evaluation in Essential oils: A review - Huda Yang; Xiaoying Huang; Ming Yang; Xiaofei Zhang; Fangrui Tang; Beibei Gao; Mengya Gong; Yong Liang; Yang Liu; Xingyi Qian; Huiting Li (Food Chemistry, 2024)

Microplastics increase the microbial functional potential of greenhouse gas emissions and water pollution in a freshwater lake: A metagenomic study - Tianyu Zhuo; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Yang Li; Yuan Meng; Lifeng Wu; Bin Chen (Environmental Research, 2024)

Rapid Joule heating-induced welding of silicon and graphene for enhanced lithium-ion battery anodes - Fan Yang; Pengcheng Deng; Hang He; Ruolan Hong; Kun Xiang; Yuan Cao; Beibei Yu; Zeman Xie; Jiming Lu; Zikang Liu; Danish Khan; David Harbottle; et al. (Chemical Engineering Journal, 2024)

Four-in-one multifunctional self-driven photoelectrocatalytic system for water purification: Organics degradation, U(VI) reduction, electricity generation and disinfection against bacteria - Sixuan Cai; Yanjun Wen; Qingyan Zhang; Qingming Zeng; Qingqing Yang; Beibei Gao; Guolong Tang; Qingyi Zeng (Science of The Total Environment, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

The cAMP receptor protein gene contributes to growth, stress resistance, and colonization of Actinobacillus pleuropneumoniae - Qiyun He; Yaxuan Zheng; Kang Yan; Jia Tang; Fengming Yang; Yanhong Tian; Lijun Yang; Beibei Dou; Yunpeng Chen; Jun Gu; Huanchun Chen; Fangyan Yuan; et al. (Veterinary Microbiology, 2024)

Benzoquinone and furopyridinone derivatives from the marine-derived fungus Talaromyces sp. MCCC 3A01752 - Xuan Hong; Lingzhi Tang; Zhongwei Chen; Qiliang Lai; Beibei Zhang; Youwei Jiang; Xunjie Wang; Ruonan He; Jianhui Lin; Zongze Shao; Shan Lin; Weiyi Wang (Natural Product Research, 2024)

Leaching of chemicals from microplastics: A review of chemical types, leaching mechanisms and influencing factors - Yage Li; Chen Liu; Haotian Yang; Wenhui He; Beibei Li; Xinyi Zhu; Shuyan Liu; Shihao Jia; Ronghua Li; Kuok Ho Daniel Tang (Science of The Total Environment, 2024)

Poly-adenine-mediated tetrahedral DNA nanostructure with multiple target-recognition sites for ultrasensitive and rapid electrochemical detection of Aflatoxin B1 - Kaixuan Wang; Nuanfei Zhu; Yumo Li; Hu Zhang; Beibei Wu; Jian Cui; Jun Tang; Zhugen Yang; Fang Zhu; Zhen Zhang (Analytica Chimica Acta, 2023)

Hydrostatic pressure drives microbe-mediated biodegradation of microplastics in surface sediments of deep reservoirs: Novel findings from hydrostatic pressure simulation experiments - Kehong Yu; Beibei Chai; Tianyu Zhuo; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Bin Chen (Water Research, 2023)

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

Solar-driven wastewater treatment coupled with hydrogen and electricity production via a bismuth-doped TiO2 nanorod array - Beibei Gao; Jing Tan; Yuhan Cao; Qingsong Zhang; Yanjun Wen; Qingming Zeng; Guolong Tang; Junwen Lv; Lin Wang; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2023)

Investigation of toxic effect of mercury on Microcystis aeruginosa: Correlation between intracellular mercury content at single cells level and algae physiological responses - Wenxiao Tang; Man He; Beibei Chen; Gang Ruan; Yixue Xia; Pingping Xu; Gaofei Song; Yonghong Bi; Bin Hu (Science of The Total Environment, 2023)

Rational design strategies for nonconventional luminogens with efficient and tunable emission in dilute solution - Ji Luo; Song Guo; Feixia Chen; Bingli Jiang; Lingzhong Wei; Yongyang Gong; Beibei Zhang; Yuanli Liu; Chun Wei; Ben Zhong Tang (Chemical Engineering Journal, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Screening and production of dsRNA molecules for protecting Cucumis sativus against Cucumber mosaic virus through foliar application - Qin Mo; Beibei Lv; Yu Sun; Xiao Wu; Lili Song; Run Cai; Xueming Tang (Plant Biotechnology Reports, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Mapping daily leaf area index at 30 m resolution over a meadow steppe area by fusing Landsat, Sentinel-2A and MODIS data - Zhenwang Li; Chengquan Huang; Zhiliang Zhu; Feng Gao; Huan Tang; Xiaoping Xin; Lei Ding; Beibei Shen; Jinxun Liu; Baorui Chen; Xu Wang; Ruirui Yan (International Journal of Remote Sensing, 2018)

The synergistic effect of 5Azadc and TSA on maintenance of pluripotency of chicken ESCs by overexpression of NANOG gene - Xiaoyan Wang; Yingjie Wang; Qisheng Zuo; Dong Li; Wenhui Zhang; Chao Lian; Beibei Tang; Tianrong Xiao; Man Wang; Kehua Wang; Bichun Li; Yani Zhang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Basing RNA-seq explored the regulatory mechanism of the carbohydrate metabolism pathways during chicken male germ cell differentiation - Chao Lian; Qisheng Zuo; Dong Li; Lei Zhang; Mahmoud F. Ahmed; Tianrong Xiao; Beibei Tang; Yingjie Wang; Kai Jin; Yani Zhang; Bichun Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Regulatory mechanism of protein metabolic pathway during the differentiation process of chicken male germ cell - Dong Li; Qisheng Zuo; Chao Lian; Lei Zhang; Qingqing Shi; Zhentao Zhang; Yingjie Wang; Mahmoud F. Ahmed; Beibei Tang; Tianrong Xiao; Yani Zhang; Bichun Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Plant growth-promoting rhizobacteria enhance the growth and Cd uptake of Sedum plumbizincicola in a Cd-contaminated soil - Wuxing Liu; Qingling Wang; Beibei Wang; Jinyu Hou; Yongming Luo; Caixian Tang; Ashley E. Franks (Journal of Soils and Sediments, 2015)

Tropane alkaloids production in transgenic Hyoscyamus niger hairy root cultures over-expressing Putrescine N-methyltransferase is methyl jasmonate-dependent - Lei Zhang; Bin Yang; Beibei Lu; Guoyin Kai; Zinan Wang; Yang Xia; Ruxian Ding; Hanming Zhang; Xiaofen Sun; Wansheng Chen; Kexuan Tang (Planta, 2007)